1988
DOI: 10.1136/pgmj.64.757.878
|View full text |Cite
|
Sign up to set email alerts
|

Follicular carcinoma of the thyroid following radioactive iodine treatment for Graves’ disease

Abstract: Summary:A 67 year old man presented with a well differentiated follicular carcinoma of the thyroid 17 years after he had been given radioactive iodine for Graves' disease. As this was insufficient to cure him he had continued to take propylthiouracil regularly. The tumour, which had completely replaced the thyroid, was apparently maintaining thyrotoxicosis. The implications of this management are discussed and it is concluded that antithyroid drugs should not be given on a long term basis after therapeutic rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…In the literature, there are few reports about thyroid cancer after RAI therapy for toxic nodulary or diffused goiter. Staffurth et al reported a folliculary thyroid cancer following RAI therapy for Graves' disease [5]. In their case, FTC derived 17 years after the RAI therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the literature, there are few reports about thyroid cancer after RAI therapy for toxic nodulary or diffused goiter. Staffurth et al reported a folliculary thyroid cancer following RAI therapy for Graves' disease [5]. In their case, FTC derived 17 years after the RAI therapy.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature, many reports have been published in terms of radiation induced thyroid malignancy after Chernobyl accident [3,4]. Likewise, it is reported that thyroid cancer can be developed after 131 I therapy for thyrotoxicos [5][6][7][8][9]. It is also reported that 131 I therapy for diagnostic purpose does not increase the risk of thyroid malignacy although it is commonly used [10].…”
Section: Introductionmentioning
confidence: 99%
“…Staffurth et al reported a follicular thyroid cancer following RAI therapy for Graves' disease [4]. In their case, follicular thyroid cancer was derived 17 years after the RAI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One of the long term side effects of ionizing radiation is the possibility of radiation induced malignancy. In the literature, there are some reports which show that thyroid cancer can develop after 131 I therapy for thyrotoxicosis [4][5][6][7][8]. As there is no reported cancer case that developed from hot nodule, routine fine needle aspiration biopsy (FNAB) is not recommended by ATA [2].…”
Section: Introductionmentioning
confidence: 99%
“…Staffurth et al reported a case of follicular thyroid cancer 15 years after a small dose of radioactive iodine (4 mCi) for Graves' disease [18]. [19] that play a significant role in thyroid carcinogenesis and angiogenesis [20].…”
Section: Discussionmentioning
confidence: 99%